Correction: Modulation of the mechanical energy storage performance of the MIL-47(VIV) metal organic framework by ligand functionalization. Issue 8 (11th February 2019) - G. Yot, Pascal; Wahiduzzaman, Mohammad; Elkaim, Erik; Fertey, Pierre; Fabry, Paul; Magnier, Emmanuel; Devic, Thomas; Serre, Christian; Maurin, Guillaume
Abstract : Correction for 'Modulation of the mechanical energy storage performance of the MIL-47(V IV ) metal organic framework by ligand functionalization' by Pascal G. Yot et al., Dalton Trans., 2019, DOI: 10.1039/c8dt04214d.